Reviewing the Competence of Architecture Students Regarding Project-Based Learning Strategies (PBL) in Architecture Courses at UiTM - Yusri, Muhammad Amirul Hakimi; Amiruddin, Mohd Hasril (Research and Innovation in Technical and Vocational Education and Training, 2025)
The project-based learning (PBL) approach has become increasingly popular in higher education institutions as a strategy that promotes deep learning, critical thinking and problem-solving skills among students. This study focuses on assessing the competence of architecture students towards project-based learning (PBL) strategies in improving the knowledge, skills and attitudes of architecture students at UiTM. Using a quantitative approach with descriptive analysis and inferential analysis of differences, the results of the study show that the average amount of architecture students’ competency constructs for project-based learning strategies (PBL) in architecture courses at UiTM reached a high level. In addition, the study found that there was no significant difference in the knowledge, skills and attitudes of architecture students based on gender. Competence in PBL strategy is obtained uniformly among male and female students. The implications of this study have a positive impact on the knowledge, skills and attitudes of architecture students. Focusing on the development of technical and soft skills, curriculum alignment with industry, and increasing positive attitudes towards PBL are the keys to effectiveness. It is necessary to increase the use of PBL with training of teaching staff, provision of resources, and adequate support. Continuous and formative assessment is important in improving the quality of PBL learning at UiTM. As a suggestion for further research, the researcher is advised to conduct a qualitative study to obtain additional information beyond the scope of this study. This study may include aspects of knowledge, skills, and attitudes, aiming to contribute to strengthening student competence through PBL strategies in teaching architecture in the future.